Evaluating Ovarian Volume as a Diagnostic Marker for Polycystic Ovary Syndrome: A Comparative Study in Iraqi Women - Al-Hamzawi, Maal Anwer (Medical Science Journal for Advance Research, 2025)
Background: One of major problems in every day obstetrics and gynecology practice is the polycystic ovarian syndrome. Despite the fact that the disease has been described since many decades; the diagnosis of the disease is still difficult. Several guidelines have been introduced to highlights the pathognomonic criteria to diagnose the disease, but, still there is debate about the adoption and interpretation of these criteria including hyperandrogenemia, ovulation and menstrual irregularities and polycystic ovarian morphology. Aim of the study: to evaluate the role of ovarian volume measured by Doppler ultrasound in prediction of PCOS diagnosis. Methodology: The study, which is of case-control design, was carried out in the Maternity and Children Teaching Hospital at Al -Diwaniyah Province, Iraq. The study included 95 women with clinical diagnosis of polycystic ovary syndrome (in accordance with Rotterdam criteria) in addition to 90 healthy control women of comparable reproductive age range. Ultrasound examination was performed for all enrolled women. Size of ovary and ovarian morphological features were assessed and contrast was made between either study category. Results: The mean volume of ovaries in PCOS women was 9.13 ±1.89 ml; whereas, that of control group was 8.16 ±1.22 ml. This variation in average ovarian volume between the two categories was statistically significant (p<0.001). The proportion of women with ovarian volume > 10 ml was greater in a significant way in PCOS category in comparison with the category of control individuals, 23.2 % versus 4.4 %, respectively (p <0.001). The cutoff value was > 9.4 ml with a specificity of 86.7 %, a sensitivity of 36.4 % and an area under curve (AUC). Conclusion: The use of ovarian volume alone is not sufficient to diagnose women with PCOS and that the used of clinical features, biochemical features, hormonal assay and ultrasound examination are all needed to label a suspected woman with such a diagnosis.